Assessment of the potential risks in SD rats gavaged with genetically modified yeast containing the cp4-epsps gene - Bi, Bo; Fu, Xuewei; Jian, Xuewen; Zhang, Yu; Jiang, Yizhi; Zhou, Wuyi; Zhao, Hui (Frontiers in Veterinary Science, 2024)
This study evaluates the potential risk of CP4-EPSPS protein in genetically modified (GM) crops. The expression level of CP4-EPSPS in recombinant yeast was quantified to establish daily dosage for gavage. A 90-day feeding experiment on Sprague-Dawley (SD) rats was conducted, with subsequent metabolomics and metagenomic analysis. The results from the physiological and biochemical analysis, organ pathological, blood metabolism, gut microbiota, and correlation analysis of metabolites and gut microbiota revealed several biomarkers for further risk assessment. These include clinical biochemical indexes such as total bilirubin (TBIL), direct bilirubin (DBIL), creatine kinase (CK), and lactate dehydrogenase (LDH); metabolites like Methionine, 2-Oxovaleric acid, and LysoPC (16:0); and gut microbiota including Blautia wexlerae, Holdemanella biformis, Dorea sp CAG 317, Coriobacteriaceae and Erysipelotrichaceae.This study also found that the risk associated with activated recombinant CP4-EPSPS can be substantially mitigated through inactivation. Thus, in routine life, the risk associated with consuming GM foods containing recombinant CP4-EPSPS is substantially reduced after heat treatment.